Development of Remote Cathodic Protection Potential Measuring System - Haslin, Muhammad Haziq; Mohamad, Khairul Anuar; Alias, Afishah; Razali, El-Farabi; Nordin, Mohammad Syahmi; Abu Bakar, Mohd Nasri (Evolution in Electrical and Electronic Engineering, 2022)
Underground pipelines are one of the most critical infrastructures in the world for transporting a liquid or gas. One major challenge in the pipeline operation is a corrosion attack that significantly contributes to high-cost maintenance. Therefore, the monitoring system needs to be improved to provide early warning to the operators and cathodic protection (CP) technicians for immediate mitigation planning and, at the same time, speed up the maintenance work. The developed device is equipped with a voltage sensor, humidity sensor and battery capacity sensor. Node-RED will be used to develop an interface to monitor all the parameters collected from the device. The findings indicate that the device could measure potential readings as precisely as a multimeter after the experiment setup was conducted. Based on the data collection, the potential readings for corrosion-free is higher than corroded steel, and the observation is conducted to study the behaviour of steel in terms of cathodic protection. To conclude, the objectives are successfully achieved in this project.